In Their Own Words: Prefaces and Other Sites of Editorial Interaction in Nineteenth-Century Canadian Magazines - Bowness, Suzanne (Université d'Ottawa / University of Ottawa, 2012)
This dissertation investigates nineteenth-century Canadian literary and general interest periodicals through the prefaces and other editorial missives written by the editors who created them. It seeks to demonstrate how these cultural workers saw their magazines as vehicles for promoting civic and literary development. While the handful of previous Canadian magazine dissertations take a “snapshot” approach to the genre by profiling a handful of titles within a region, this study attempts to capture the editorial impulse behind magazine development more widely. To do so, it examines multiple titles over a wider geographical and chronological span. To provide context for these primary documents, the dissertation begins with a chapter that summarizes the development of magazines as a genre and the history of publishing in nineteenth-century Canada. Subsequent chapters examine prefaces by theme as well as by rhetorical strategy. Themes such as nationalism, cultural development, and anti-Americanism emerge most prominently, alongside rhetorical techniques such as metaphor, imagery, analogy and personification. The dissertation also examines other sites of editorial interaction, most commonly the “correspondent’s columns,” where editors provided public feedback on topics ranging from versification to currency to prose style as a means of educating writers and readers alike. Finally, the dissertation relies on existing indexes to identify some of the most prolific contributors to the magazines, considering how these writers used the magazines to boost their literary careers. In the early century, these sources verify the productivity of canonical writers such as Susanna Moodie and Rosanna Leprohon, and call attention to obscure writers such as Eliza Lanesford Cushing, W. Arthur Calnek, James Haskins, and Mary Jane Katzmann Lawson. In the later century, the same approach is used again to examine the hive of writers who emerged to contribute to late century magazines like The Canadian Monthly and National Review and The Week, confirming the immense productivity of writers such as Agnes Maule Machar and drawing attention to now-obscure contributors like Mary Morgan. By recovering these overlooked editorial elements and figures, this dissertation draws scholarly attention to a more nuanced view of literary production and affirms the importance of magazines to literary development in nineteenth-century Canada.
Keywords: nineteenth-century Canadian magazines; magazine history; Canadian magazines; Canadian periodicals; publishing history Canada; Canadian magazine history